An Implicit Projected Argument in Spanish Impersonal‐ and Passive‐Se Constructions. (23rd October 2017) - MacDonald, Jonathan E.
Abstract: This article argues for the presence of an implicit projected argument in Spec, Voice in Spanish impersonal‐ and passive‐ se constructions. The main empirical support comes from an available inalienable‐possession interpretation of the sole overt DP when it is a body part in both constructions. This interpretation is only possible in the presence of a syntactically present c‐commanding possessor. I argue that the implicit projected external argument serves as the inalienable possessor of the body part. Neither the periphrastic passive nor the anticausative‐ se construction in Spanish allows an inalienable‐possession interpretation of the sole overt DP when it is a body part. In these instances, I claim, no implicit argument projects in Spec, Voice. I discuss how the presence of a projected argument in Spec, Voice is responsible for by ‐phrase restrictions in impersonal‐ and passive‐ se constructions and person restrictions in passive‐ se constructions; the lack of a projected implicit argument in Spec, Voice of both the periphrastic passive and the anticausative‐ se construction is responsible for the lack of the person restrictions in both, and the lack of by ‐phrase restrictions in the periphrastic passive.